Hermeneutic of the Theology of Liberation: Community and Freedom - Andrei MELESHKO (Богословські роздуми: Східноєвропейський журнал богословʼя)
In the article author considers the hermeneutical approach of the Liberation Theology with purpose to find main elements which have influenced in this approach. Author shows historical background of the movement and analyzes views on interpretation of the Bible, role of community in this process, and points some strengths and weaknesses of this approach. Also author gives few brief comparisons with practices of interpretation of the Scripture which exist in Baptist churches.